Criminal Liability for Cryptocurrency Transactions: Global Experience - Cherniei, Volodymyr; Cherniavskyi, Serhii; Babanina, Viktoria; Tykho, Оlena (European Journal of Sustainable Development, 2021)
The article examines the features of criminal liability for transactions related to the circulation of cryptocurrencies. In order to determine the specifics of criminal violations in the field of cryptocurrency circulation, the legal nature of cryptocurrencies is studied. It is concluded that in order to properly qualify criminal offenses related to the circulation of cryptocurrencies, it is advisable to recognize cryptocurrencies as a type of property or money. The article analyzes the global approaches to the legal regulation of relations related to the circulation of cryptocurrencies. Based on the results of this analysis, it is concluded that relations regarding cryptocurrencies in most countries of the world are insufficiently regulated and are still outside of the legal field. This complicates, inter alia, the establishment of criminal liability for transactions involving the circulation of cryptocurrencies. A significant part of the article is devoted directly to the study of criminal liability for transactions involving the circulation of cryptocurrencies in different countries. The norms of the Criminal Codes, which establish liability for criminal violations in the field of cryptocurrency circulation, are analyzed. The measures that need to be implemented to ensure the control of government agencies over the circulation of cryptocurrencies and the security of all operations related to cryptocurrencies are identified.